Implications of Teacher Personality Competence Based on Titus 2:6-8 for Sunday school Teachers - DARMAWAN, I Putu Ayub; SITEPU, Ria Ferdika Br; YULIANTI, Sri; RAIDIFI , Elwandy; PERANGIN-ANGIN, Darni Br (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2023)
Every community, culture, and nation are competing to develop an educational system that is based on a solid foundation of information, learning, ethics, and competence. Thus, in the modern world, a nation with a strong educational system will thrive and influence the rest of the globe. However, in the educational system, only competent and qualified teachers can deliver quality education. This implies that an individual teacher’s personality abilities will impact how they interact with their students. The study investigated the extent to which the teacher’s personality competency in Titus 2:6–8 related to Sunday school teachers. This study examines the context of Paul’s epistle to Titus using the Biblical hermeneutics research approach. The teacher’s personality competencies were then assessed using the textual analysis method. For this research, Bible encyclopaedias, commentaries on the Epistle to Titus, and research articles from scholarly publications were employed as references. The findings of the analysis are presented in a meta-narrative and descriptive fashion. According to this work, the teacher’s personality competency stated in Titus 2:6–8 sets a positive example for students to follow, most notably encouragement in remaining steadfast in faith in Christ Jesus and the ability to inspire students to understand and practise moral ethical values as well as demonstrate modesty in behaviour. This research also contends that the teacher’s personality competency, as mentioned in Titus 2:6–8, demonstrates acceptable conduct since children are more prone to emulate actions than words, and that the teacher possesses high levels of dedication and commitment to the Sunday school students.